Logical Form in Natural Language - Lycan, William G. (London Bradford, 1986)
In this book, a well-known and highly respected philosopher details the complicated anatomy of linguistic meaning, showing how its elements fit together; he explores the interface between "languages" considered as formal systems and the linguistic activities of human beings in speech situations; and he defends the autonomy of linguistic semantics as a branch of scientific psychology.The book's first Part sets out and defends the truth-theoretic method in semantics, arguing that the notion of a sentence's truth-condition lies at the core of meaning.Part Two considers a number of apparent differences between formal and natural languages, having chiefly to do with the context-bound features of natural-language semantics, and attempts to reconcile them. It provides a definite focus to the semantics/pragmatics distinction, and argues that few if any of the pragmatic phenomena investigated by linguists will need to be represented in semantic theory. The author offers plausible and in some cases novel solutions to the technical problems that have plagued the semantics/pragmatics border.Part Three portrays the role of semantics in psychology and the relation of semantics to human speakers' internal functional organization. Further, the author shows how a sentence's truth-condition meshes with each of the other aspects of its meaning, and argues that traditional theories of meaning which have focused on some of these other aspects should be regarded as mutually complementary components of linguistic theory rather than being treated as rival accounts of a common subject-matter.William G. Lycan is Professor of Philosophy at the University of North Carolina, Chapel Hill. A Bradford Book.